Linkage of Technological Innovation toward ICT base and Economic Output in CLMV Region - Chhorn, Theara (Thammasat Review of Economic and Social Policy, 2018)
The Fourth Industrial Revolution will change not only what we do but also who we are. It will affect our identity and all the issues associated with it (Schwab, 2016). The state of rising technological innovation and progress of the ICT-based era of modernization and globalization, particularly in developing countries, is driving the global economy into a new structure of transitional development and transformation. The paper examines the impacts of technological progress on economic output in the CLMV region from 1995 to 2016. The conventional estimation approaches of RE, MLE-RE, FE and FGLS estimation with/without robust standard error, provide accurate and consistent empirical outcomes. The crucial impact of technological progress, internet server connections and ICT and computer import products as proxies, is found to boost economic output and generate growth rate in the CLMV region. The findings suggest that policymakers should direct policy towards investment, trade in technology, and diversification to facilitate flows of capital, goods, and services, and support bringing business structures in line with technological innovation.